Hubungan Body Image dan Restrained Eating dengan Status Gizi Kurang Mahasiswa Destinasi Pariwisata Universitas Airlangga - Vanesya Diva Rosita; Dini Ririn Andrias (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Undernutrition remains a pressing issue among university students, particularly in tourism programs that emphasize physical appearance. This study aimed to examine the relationship between body image and restrained eating with undernutrition among students of the Tourism Destination Study Program at Universitas Airlangga. A cross-sectional design was employed involving 114 students from the 2024–2025 cohorts selected through proportionate stratified random sampling. Body image was measured using BSQ-16, restrained eating was measured using DEBQ, and nutritional status was determined based on BMI. The results showed that most respondents had negative body image, practiced restrained eating, had inadequate macronutrient intake, and were classified as having normal nutritional status. Statistical analysis revealed significant associations between body image and restrained eating with undernutrition, but in an inverse pattern. Students with undernutrition were more likely to have a positive body image and engage in unrestrained eating, whereas students with normal to excess nutritional statuses tended to have negative body images and practice restrained eating. These findings indicate that students in the tourism field tend to prioritize ideal body standards over objectively evaluating their bodies based on health indicators.